Cultures of Computer Game Concerns (transcript Verlag, 2021)
The same computer games are played by youths all over the world, and worldwide games become matters of concern in relation to children: worries rise about addiction, violence, education, time, and economy. Yet, these concerns vary depending upon where they are situated: in families, legal contexts, industry or science. They also play out differently across countries and cultures. This situated nature of computer game concerns is generally neglected. Not in this book: It gives a detailed mosaic of the complex and multiple everyday realities of computer game concerns in relation to children, as they are variably situated throughout society and across cultures.